I remember nothing and other reflections - Ephron, Nora 1941-2012 (Vintage Books, 2012)
A humorous collection of personal essays discusses the author's career in journalism, divorce, a long-anticipated inheritance with unanticipated results, and the evolution of her relationship with her e-mail in-box